Controlled nanostructure of a graphene nanosheet‐TiO2 composite fabricated via mediation of organic ligands for high‐performance Li storage applications. (20th May 2021) - Hwang, Keebum; Kim, Nayoung; Jeong, Yohan; Sohn, Hiesang; Yoon, Songhun
Summary: A graphene nanosheet‐TiO2 nanoparticle composite (L‐GNS‐TiO2 ) was prepared for an application as a high‐performance lithium storage device (or lithium‐ion battery anode). The composite features a well‐defined hybrid structure of GNS and homogeneously distributed anatase TiO2 nanoparticles due to nanoparticulation and modification by organic ligands (polyacrylic acid, tartaric acid, and diethylene glycol). Despite its low overall carbon content (~8.4%), the L‐GNS‐TiO2 composite‐based anode exhibited highly reversible lithiation/delithiation (Coulombic efficiency >97%), excellent capacity retention (206 (92%) and 331 (147%) mAh g −1 after 50 and 450 cycles, respectively, at 0.15 A g −1 ) and decent rate capability (164 mAh g −1 at 0.75 A g −1 ). In addition, the stable morphology/structure of the composite after lengthy cycle tests reflected its mechanical robustness and electrochemical reversibility. The excellent performance of L‐GNS‐TiO2 was attributed to the enhanced electronic conductivity, retained charge storage sites, and a short Li + diffusion pathway enabled by the unique composite structure constructed through optimized ligand mediation. Highlights: A graphene nanosheet‐TiO2 nanoparticle composite (L‐GNS‐TiO2 ) was prepared for Li storage applications. L‐GNS‐TiO2 possesses a structure containing uniformly distributed anatase TiO2 nanoparticles on GNS due to optimized mediation and nanoparticulation by organic ligands. L‐GNS‐TiO2 exhibits enhanced conductivity, retains charge storage sites, and facilitates Li + transport/charge transfer. Excellent cycle stability (>100% capacity retention, 331 mAh g −1 ) and Coulombic efficiency (>99%) were realized after 450 cycles at 0.15 A g −1 . Decent rate capability was achieved with a high capacity (164 mAh g −1 ) at 0.75 A g −1 .